Neuroplasticity in amputees: Main implications on bidirectional interfacing of cybernetic hand prostheses - Di Pino, G.; Guglielmelli, E.; Rossini, P.M. (Progress in neurobiology, 2009)
The development of a new generation of hand prostheses that can ideally approximate the human 'physiological' performance in terms of movement dexterity and sensory feedback for amputees still poses many open research challenges. The most promising approaches aim at establishing a direct connection with either the central or the peripheral human nervous system by means of invasive or non-invasive neural interfaces. This paper starts from the assumption that a major contribution to derive functional and technical specifications for such interfaces, and even for the whole prosthetic system, can stem from in-depth analysis of the nervous system reorganization following limb amputation. Neuroplasticity can be modulated by the use of hand prostheses both in the acute phase and in the long-term. We hereby critically review the literature concerning neuroplastic phenomena in amputees, in terms of changes at different CNS levels, particularly for their implications on the development of bidirectional neural interfaces for cybernetic hand prostheses. Our analysis of the literature demonstrates that: (1) the level of CNS reorganization could be used as a parameter of the effectiveness achieved by the prosthetic device and its interfaces, in restoring the hand physiological functionality, (2) the prosthetic system could be seen as a neurorehabilitation tool, as it could induce reduction in aberrant plasticity and promote 'good' plasticity and (3) new generations of 'natural' interfaces can be developed by fully exploiting neuroplastic phenomena to restore neural connections originally governing the lost limb and linking them to the prosthetic system.